Development of the LARESI Teaching Factory Learning Model: Industry-Based Instructional Design to Strengthen Vocational Competencies in Vocational High Schools - La Resi; Muhammad Yahya; Syafiuddin Parenrengi (Jurnal Teknologi Pendidikan, 2026)
The Teaching Factory (TEFA) is a vocational learning approach designed to strengthen the connection between schools and the industrial sector through learning experiences that mimic real-world work environments. However, the implementation of TEFA in the Motorcycle Engineering and Business (TBSM) vocational program still faces various challenges, particularly the lack of a learning framework capable of systematically integrating customer service, damage analysis, repair processes, evaluation, handover of results, and investigation. This study aims to develop the LARESI (Service, Analysis, Implementation, Evaluation, Handover, Investigation) Teaching Factory learning model to strengthen the vocational competencies of vocational high school students. The study employed the Research and Development (R&D) method by integrating the Borg & Gall, ADDIE, 4D, Dick and Carey, and Kemp models. The research stages included needs analysis, model development, pilot testing, and validation. The research subjects were students in the TBSM Specialization Program at SMKS Satria Kendari. The results showed that the model’s development met 66.67% of the identified needs, while expert validation yielded a score of 87.50% (highly valid), practicality of 83.33% (practical), and effectiveness of 88.89% (highly effective). Implementation of the model also increased the average learning outcomes from 61.17% to 82.17%, with an N-gain of 0.58 (moderate category), raised the graduation rate from 20% to 85%, and yielded a statistically significant difference (t = 11.917; p < 0.001). These findings indicate that the LARESI Teaching Factory model is suitable for implementation as an industry-based vocational learning model capable of integrating technical and non-technical competencies through a comprehensive workshop service cycle, thereby potentially enhancing the work readiness of vocational high school graduates.